Sistem Pakar Mendiagnosa Penyakit Pada Kelinci Dengan Menggunakan Metode Dempster Shafer - Dorkas Sianturi (STMIK Budi Darma, 2019)
Skin disease in rabbits is one of the diseases that are often experienced by rabbits, one of which is Demodexcosis. The main cause is the attack of parasites or fleas that are very small in size. This disease can attack rabbits as well as adults. Symptoms that arise from demodexcosis are skin redness, thickening of the skin and swollen follicle fur, disrupted growth. However, many people experience difficulties due to the lack of knowledge about various diseases that attack rabbits and the inadequate and healthy rabbit feed. To detect a disease that is being overwritten and thus we can take the right steps to treat it without bringing the animal to an expert or veterinarian. In this case the expert system can provide knowledge designed to model the problem solving ability like an expert. An expert system was developed in order to be able to assist the tasks of experts with the help of a system that has knowledge, without having to have an expert working in that place. There are several methods that can be applied in expert systems, and one of them is the dempster shafer method. Dempster shafer is one of the mathematical theories to prove hypotheses based on belief functions and plausible reasoning, which are used to combine separate pieces of information or evidence to calculate the probability of an event. The application that will be used in building this system is PHP using a MySQL database.